Peningkatan Kandungan Protein Mi Instan dari Substitusi Tepung Jagung dengan Tepung Kacang Hijau - Meda Canti; Sri Anggrahini; Priyanto Triwitono (Jurnal Ilmu Pangan dan Hasil Pertanian, 2018)
The efforts to diversify food products can be done by substitution of wheat flour with corn flour on instant noodle. Protein content of corn flour is low, so it is added with mungbean flour. The aim of this research was to increase protein content of instant noodle by substitution of corn flour with addition of 0-20% mungbean flour and to evaluate the physical, sensory and chemical properties of instant noodles. This study was preceded by a reduction phytate content on mungbean flour with boiling and soaking. Ratio of wheat flour and corn flour as control of 8:2. The addition of mungbean flour of 0%, 5%, 10%, 15% and 20%. Instant noodles were analyzed for physical, sensory and chemical properties. The result show that boiling treatment of mungbean decreased the phytate content higher than soaking treatment. Rehydration capacity, expansion ratio, flavor, elasticity of instant noodles with added of soaked mungbean flour of 5-20% and boiled mungbean flour of 5-10% same as control instant noodles. Instant noodle with added of soaked mungbean flour of 20% was able to increase protein content 1.38 fold with protein content 13.14% db, while with added of boiled mungbean flour of 10% was able to increase protein content 1.13 fold with protein content 10.82% db. Keywords : instant noodle; wheat flour; corn; mung bean; protein